Optimization and Process Parameters of CNC End Mill ing For Aluminum Alloy 6082 - K. Siva Kumar; Bathina Sreenivasulu (International Journal of Innovations in Engineering Research and Technology, 2021)
The study aims at optimization of cutting parameters in CNC Endmilling of Aluminum Alloy 6082. CNC millingis a versatile and most widely used operation in present industry. Surface quality affects fatigue life ofcomponents and influences various mechanical properties and has received serious attention for many years. Inthis work, experiments are conducted to analyze the surface roughness using various machining parameters suchas Spindle speed, feed rate and depth of cut .